PERMAINAN JUDI TANPA IJIN SEBAGAI MATA PENCARIAN DALAM PERSPEKTIF HUKUM PIDANA - Bima Prayogi Prilisciatama (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACTThe rise of gambling at this time makes a big loss on the next young generation of the article with gambling people becoming lazy to work, looking for a fortune by complaining an uncertain fate, gambling activities since ancient times have never brought prosperity to the perpetrators. Profit Gambling Games Without Permission As A Search In The Criminal Law Perspective, the research method used is Normative juridical, using this type of research the author tries to describe a situation that is the object of research. Gambling crimes can be formulated in two articles namely Article 303 and 303 buses. These two articles constitute a crime, among others, is the crime of offering or providing an opportunity to play gambling and use the opportunity to play gambling together with other people. The author hopes that the local government and law enforcement have the same vision and work together to eradicate gambling crime in Samarinda City. Keywords: Gambling, Eye Search and Criminal Law